2014
DOI: 10.1002/jmor.20298
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spermatozoa of orsolobidae (Haplogynae, Araneae) with implications on the evolution of sperm transfer forms in Dysderoidea

Abstract: Haplogynae are highly diverse with respect to the primary male genital system and sperm characteristics. Additionally, all sperm transfer forms (STF) known for spiders are present. Besides individually transferred sperm (cleistospermia), sperm are transferred as conjugates, both primary (synspermia) and secondary sperm conjugates (coenospermia, rouleaux) occur. Nevertheless, the ultrastructure of spermatozoa and STF are described for few Haplogynae and often only one representative species was studied, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Spider sperm need to be activated within the female reproductive system by female secretory products (Uhl, 1993;Herberstein et al, 2011b;Vö cking et al, 2013). Consequently, unsheathed sperm might bypass an initial triggering and avoid a direct female choice, as suggested by Lipke et al (2014). However, in this case the putative protective function during sperm induction and transfer into the female genital system should be correlated with additional secretions that achieve a protection during sperm induction and transfer (Lipke et al, 2014).…”
Section: Evolutionary and Functional Implicationsmentioning
confidence: 94%
See 3 more Smart Citations
“…Spider sperm need to be activated within the female reproductive system by female secretory products (Uhl, 1993;Herberstein et al, 2011b;Vö cking et al, 2013). Consequently, unsheathed sperm might bypass an initial triggering and avoid a direct female choice, as suggested by Lipke et al (2014). However, in this case the putative protective function during sperm induction and transfer into the female genital system should be correlated with additional secretions that achieve a protection during sperm induction and transfer (Lipke et al, 2014).…”
Section: Evolutionary and Functional Implicationsmentioning
confidence: 94%
“…Recently, Lipke et al (2014) analyzed several representatives of Orsolobidae and revealed postcentriolar elongations having a similar length as the precentriolar part of nucleus, while the axoneme is longer than the precentriolar part of nucleus. The present study further complements knowledge on this issue (see table 1).…”
Section: Evolutionary and Functional Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Authors: Lipke, E., Ramírez, M. J. and Michalik, P Data type: multimedia Brief description: Orsolobus pucara (Orsolobidae), from Lipke et al (2014). This PDF file contains interactive 3D content.…”
Section: Author Contributionsmentioning
confidence: 99%